La influencia del modelo de Alejandro Magno en la tradición escipiónica - Torrecarav Pagola, Elena (Gerión. Revista de Historia Antigua, 2003)
The archetype of the conqueror built from the historical figure of Alexander the Great exerted a remarkable influence on the historiography about the Cornelil Scipiones who, this way, turned into Roman versions of the kosmókrotor.